2007
DOI: 10.1016/j.compositesa.2006.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Porous nanocomposites prepared from layered clay and PMMA [poly(methyl methacrylate)]

Abstract: The aim of the present work is the preparation of PMMA based porous nanocomposites that contain clay (montmorillonite, MMT) platelets as reinforcements within the cell walls of the porous structure. To render the clay layers organophilic, MMT was surface treated by an ion exchange reaction between interlayer cations of the clay and ammonium ions of a surfactant. Clay/PMMA based porous nanocomposites were prepared by polymerization of water-in-oil emulsions with and without clay addition. The microstructure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…Its main disadvantages are the instability of color, poor resistance to wear and tear, volume shrinkage after the polymerization, oral mucosa irritation, and aging, and staining or discoloration relatively easily occurs [3]. Nowadays, most products for dental restoration have been produced from acrylic resins based on heat-cured PMMA, due to its optical properties, biocompatibility, and aesthetics [52,53]. However, it has a long-standing drawback that is lack of strength particularly under fatigue failure inside the mouth and also shows low abrasion resistance and microbial adhesion onto PMMA to long-term PMMA wearers.…”
Section: Nanoresin Based Materials In Prosthodonticsmentioning
confidence: 99%
“…Its main disadvantages are the instability of color, poor resistance to wear and tear, volume shrinkage after the polymerization, oral mucosa irritation, and aging, and staining or discoloration relatively easily occurs [3]. Nowadays, most products for dental restoration have been produced from acrylic resins based on heat-cured PMMA, due to its optical properties, biocompatibility, and aesthetics [52,53]. However, it has a long-standing drawback that is lack of strength particularly under fatigue failure inside the mouth and also shows low abrasion resistance and microbial adhesion onto PMMA to long-term PMMA wearers.…”
Section: Nanoresin Based Materials In Prosthodonticsmentioning
confidence: 99%
“…To date, up to 95% dental prostheses are composed of Poly(Methyl MethAcrylate) (PMMA), due to its advantages, including its optical properties, biocompatibility, and aesthetics [1,2]. However, important issues are still to be addressed in order to improve acrylic polymers properties for artificial dentures.…”
Section: Introductionmentioning
confidence: 99%
“…Its discovery has been recognized as an historical milestone in the development of nanomaterials. Now, MMT has been applied in many polymers, such as polyacrylate ester, 1,2 poly (methyl methacrylate), 3,4 polyurethane, 5,6 epoxy, 7,8 polyethylene, 9,10 and polypropylene, 11,12 etc. Ding et al [13][14][15][16] also reported the application in PVAc, but they mainly focused on the preparation of PVAc-MMT initiated by g-ray radiation intercalation polymerization and the co-blending of PVAc-MMT with high density polyethylene.…”
Section: Introductionmentioning
confidence: 99%